Pendidikan Karakter Sebagai Pilar Utama Peningkatan Kualitas Dunia Pendidikan - Ilham Kamaruddin; Dede Ibrahim Muthawali; Trisna Rukhmana; Yohanis Hukubun; Budi Mardikawati; Uki Hares Yulianti (Departement of Mathematics Education, 2024)
Character education has become a major concern in efforts to improve the quality of education. In the context of the dynamics of the times that continue to develop, character education has an undeniable role in forming quality individuals who are able to contribute positively to society. This research explores the concept of character education as the main pillar in improving the quality of education. Through a qualitative approach, we analyzed awareness of the importance of character education, challenges in implementing it, and effective strategies in making it happen. The research findings highlight the need for collaboration between various educational stakeholders, the development of innovative strategies, and a continued commitment to creating an inclusive, ethical, and quality educational environment.